Cochlear resident macrophage mediates development of ribbon synapses via CX3CR1/CX3CL1 axis - Song, Xinyu; Li, Yang; Guo, Rui; Yu, Qianru; Liu, Shan; Teng, Qi; Chen, Zhong-Rui; Xie, Jing; Gong, Shusheng; Liu, Ke (Frontiers in Molecular Neuroscience, 2022)
Cochlear ribbon synapses formed between spiral ganglion neurons and inner hair cells in postnatal mice must undergo significant morphological and functional development to reach auditory maturation. However, the mechanisms underlying cochlear ribbon synapse remodeling remain unclear. This study found that cochlear resident macrophages are essential for cochlear ribbon synapse development and maturation in mice via the CX3CR1/CX3CL1 axis. CX3CR1 expression (a macrophage surface-specific receptor) and macrophage count in the cochlea were significantly increased from postnatal day 7 then decreased from days 14 to 28. Seven-day treatment with CX3CR1 inhibitors and artificial upregulation of CX3CL1 levels in the inner ear environment using the semicircular canal injection technique were initiated on day 7, and this resulted in a significant increase in hearing threshold on day 28. Additionally, abnormalities in the morphology and number of cochlear ribbon synapses were detected on day P14, which may be associated with hearing impairment. In conclusion, macrophage regulation of cochlear ribbon synapse remodeling via the CX3CR1/CX3CL1 axis is required during hearing development and offers a new perspective on immune-related hearing loss throughout auditory development. Importantly, it could be a new treatment target for sensorineural hearing loss.